PERSEPSI ULAMA NU BLORA TERHADAP BATAS MINIMAL USIA PERKAWINAN DALAM UU NO 16 TAHUN 2019 - Saidatul Chumayro (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
This study aims to describe the perceptions of the ulama of Nu Blora regarding the age limit for marriage stipulated in Law No. 16/2019. The emergence of this new provision raises a difference of opinion, especially among the ulama, which basically the provisions for the permissibility of marriage in Islam have reached baligh only without mentioning age. This research was conducted in Blora Regency with descriptive qualitative research and empirical juridical approach. The data was obtained by conducting interviews with Ulama Nu Blora and then describing it by means of data reduction, data presentation, and conclusions. The results obtained are the opinions of ulama who agree, disagree, and moderate ulama (not fully agree and disagree) against the law. Scholars who agree consider the regulation to be very beneficial for the community because in the household there is a need for emotional and financial preparedness. However, not all scholars can accept these rules, there are some who remain principled with Islamic law, namely the principle of baligh. They assume that if the marriage is delayed it is feared that an adultery will occur, especially seeing the promiscuity that occurs in the current era. Then moderate scholars argue that in implementing the law, they must look at the madharat and mashlahat aspects. Based on these results, the author specifically concludes that preparing mentally, physically and materially is very important because when we dare to get married, we are ready to be responsible for our rights and obligations after marriage.